Motives underlying smoking in college students with ADHD. (4th May 2017) - Murphy, Kerrie Glass; Flory, Kate
ABSTRACT: Background . The positive association between attention deficit hyperactivity disorder (ADHD) symptoms and smoking in youth has been well documented. Less research has examined why individuals with ADHD, particularly college students, are at increased risk for smoking. Objectives . This longitudinal study examined whether smoking motives [cognitive enhancement, tolerance, negative reinforcement (smoking to reduce negative affect or stress), craving, social influences, and weight control] helped to explain the relation between ADHD symptoms (inattention and hyperactivity/impulsivity) and cigarette smoking among college students. Methods . Participants were 889 undergraduates (21% men) and their parents who completed online surveys at the beginning and end of the Fall semester regarding their smoking behaviors, ADHD symptoms, and smoking motives. Structural equation modeling was used to analyze data and answer research questions. Results . Nineteen percent of students reported smoking, while 20% reported one or more inattentive symptoms, 35% reported one or more hyperactive/impulsive symptoms, and 3.3% met criteria for ADHD. All smoking motives significantly moderated the relation between inattentive symptoms and smoking, while most smoking motives (negative reinforcement, tolerance, craving, cognitive enhancement, and weight control) moderated the link between hyperactive/impulsive symptoms and smoking. Results remained significant after controlling for stimulant medication use and conduct disorder symptoms. Conclusions/Importance . Addressing negative reinforcement, craving, social influences, and tolerance in prevention and intervention efforts on college campuses may reduce smoking. Results also highlight the importance of assessing a range of ADHD symptoms in college students as ADHD symptoms, even at subthreshold levels, were associated with increased smoking rates among college students.